(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The research topic tackled knowledge sharing and its role in achieving competitive advantage for the healthy organizations, The research sought to achieve several objectives, the most important of which was (Knowledge of the importance of knowledge sharing and the competitive advantage of the organization as one of the vital variables important to the life of all organizations, including health organizations, And diagnose the nature of relationships of the correlation and effect between the knowledge sharing and competitive advantage In the surveyed hospital . Due to the importance of the health sector and its role in meeting the health and safety requirements, The research was carried out in (The Women and Obstetrics Hospital / Holy Karbolaa), where the research was conducted on a sample of (85) people working in various positions within the administrative staff of the surveyed hospital . The research was based in its practical framework on the questionnaire to acquire data and information. In order to process these data and information, the researchers used a set of statistical methods (Alpha Cronbach test, weighted mean, standard deviation, variance coefficient, response strength, correlation coefficient, simple linear regression, Interpretation coefficient R2 , F test, and T test) . The study concluded with a number of conclusions, the most important of which are (the interest of the hospital in all variables and the dimensions of the research subject, The existence of correlation and effect relationships between all search variables with their sub-dimensions), The research also led to several recommendations, the most important of which is the (necessity of directing the hospital leadership to reduce the Obstacles, constraints and barriers that prevent the transmission, exchange and participation of knowledge among all departments and people of the hospital, and provide the necessary professional requirements at the human and technological level